Role of serum ferritin level on overall survival in patients with myelodysplastic syndromes: Results of a meta-analysis of observational studies. - Claudia Pileggi; Maddalena Di Sanzo; Valentina Mascaro; Maria Grazia Marafioti; Francesco Saverio Costanzo; Maria Pavia (PLoS ONE)
Background The role of serum ferritin (SF) as a prognostic factor has been analyzed in patients with myelodysplastic syndromes (MDS) who have undergone hematopoietic stem cell transplantation (HSCT), but the prognostic role of elevated SF levels is still controversial in lower risk MDS patients. Therefore, we performed a meta-analysis of all available published literature to evaluate whether elevated SF levels are associated with a worse overall survival (OS) among patients with low risk MDS. Material and methods A systematic bibliographic search of relevant studies was undertaken in accordance with guidelines for meta-analysis of observational studies in epidemiology. Electronic databases were searched through July 2016 for studies examining the level of SF as a prognostic factor in the adults affected by MDS. Results Six articles were included in the meta-analysis. A significant association between OS and SF was achieved for the threshold of SF≥1000 ng/mL, when the only study that used SF cut-off ≥2000 ng/mL was not included in the meta-analysis (RR = 1.33; 95% CI = 1.06-1.67). The estimated risk was 2.58 (95% CI = 1.41-4.74) when a SF cut-off≥500 ng/mL was considered. Conclusions Our findings underlined a worse survival in patients with MDS who had higher SF levels. The association was stronger and achieved statistical significance after stratification of analyses in which we excluded cut-offs of SF level considered as outliers. These results suggest that negative impact on OS already exist at SF level ≥500 ng/mL. Prospective studies, are needed to better understand this relationship and, above all, to clarify whether earlier iron chelation therapy could improve patients' OS.